The Digital Paradox: Increased Connectivity and the Decline in Student Attitudes - Priawasana, Endra (Indonesian Journal of Instructional Media and Model, 2024)
In the contemporary educational landscape, digital technology has become ubiquitous, promising enhanced learning experiences and improved academic performance. This study investigates the paradoxical relationship between increased digital connectivity and the decline in student attitudes toward learning. The primary aim is to explore how extensive use of digital devices and social media impacts students' engagement, motivation, and overall academic outlook. A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews with high school students across various socioeconomic backgrounds. The data reveals a significant correlation between high levels of digital connectivity and negative shifts in students' attitudes. Specifically, students reporting higher usage of digital devices exhibited lower levels of motivation, increased feelings of distraction, and a general disengagement from academic activities. The study concludes that while digital tools offer numerous educational benefits, their overuse can lead to detrimental effects on student attitudes. This finding contributes to the education field by highlighting the need for balanced digital integration strategies that foster positive student engagement and attitudes toward learning. The research underscores the importance of developing educational policies and practices that mitigate the adverse effects of digital overconnectivity while leveraging its potential benefits.